A metabolic profile of all-cause mortality risk identified in an observational study of 44,168 individuals - Joris Deelen (Nature Portfolio, 2019)
Biomarkers that predict mortality are of interest for clinical as well as research applications. Here, the authors analyze metabolomics data from 44,168 individuals and identify key metabolites independently associated with all-cause mortality risk.